Pengaruh Kegiatan Ekstrakurikuler Muhadharah Terhadap Kemampuan Komunikasi Siswa Kelas IX SMPN 5 Bukittinggi - Ashabil Jannah; Supriadi Supriadi (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This research is based on the results of an initial survey which proves that communication skills are lacking in class IX students at SMPN 5 Bukittinggi, this can be seen from when the teacher points to students to come forward, students refuse and prefer to point to their friends, students who remain silent when the teacher asks, and when forming discussion groups, only certain students are able to express their opinions, while muhadharah activities are activities that can train students' communication skills because in muhadharah activities students are always trained to stand in front of an audience to convey an idea, this is the attraction of researchers in this research so that The research objectives can be formulated as follows: (1) To determine the effect of muhadharah on the communication skills of class IX students at SMPN 5 Bukittinggi. (2) To find out what obstacles students face in muhadharah at SMPN 5 Bukittinggi. This research is located at SMPN 5 Bukittinggi. This data was collected using observation techniques. This research uses a Quasi experimental design type of research. This research design uses a pretest only design, namely an experimental design in the field of research that involves separating the experimental group and the control group. This design involves two classes, namely the experimental class. Before any treatment is carried out in the experimental group, initial observations need to be made which are called initial observations. After treatment, the experimental group needs to be re-observed with the aim of finding out what changes have occurred in the two groups after treatment. The results of this research show that. First, the implementation of muhadharah activities at SMPN 5 Bukittinggi, namely students giving speeches in front of their friends using free materials, guided by the presenter, opened with the reading of the holy verses of the Koran and sholawatan, followed by speeches and finally filled with remarks and prayers. by the teacher. Second, before the muhadharah activity was held, students' communication skills were low. After the muhadharah activity was held and the exercises given by the teacher, the students' communication skills and courage increased. Based on the muhadharah extracurricular activities table, there is a significant influence, namely sig. 0.000 < 0.05 then H0 is rejected and H1 is accepted. It can be concluded that extracurricular muhadharah has an influence on students' communication skills.